2012
DOI: 10.3899/jrheum.120316
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Fractures in Ankylosing Spondylitis Are Associated with Lower Bone Mineral Density in Both Central and Peripheral Skeleton

Abstract: VF in AS are common but are often not diagnosed. VF are associated with advanced age, longstanding disease, impaired back mobility, syndesmophyte formation, and lower BMD in both the central and peripheral skeleton. BMD in the femoral neck, total hip, and estimated vBMD showed the strongest association with VF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 34 publications
3
63
0
2
Order By: Relevance
“…The reported prevalence rates of osteoporosis in patients with AS range between 19 and 62 %, with this high variability mainly attributed to technical difficulties in assessing spinal bone mineral density, that can result falsely elevated in AS due to ligament ossification, sclerosis of the vertebral margins, and syndesmophytes formation [8,18,[23][24][25][26][27]. More recent prospective data on osteoporosis have shown prevalence rates between 21 and 25 % [10,18,28,29]. Loss of bone mineral density may occur even in early stages of the disease in connection with the inflammation process, independent of spine mobility and exercise [4,7,30].…”
Section: Spinal Remodeling In Asmentioning
confidence: 97%
“…The reported prevalence rates of osteoporosis in patients with AS range between 19 and 62 %, with this high variability mainly attributed to technical difficulties in assessing spinal bone mineral density, that can result falsely elevated in AS due to ligament ossification, sclerosis of the vertebral margins, and syndesmophytes formation [8,18,[23][24][25][26][27]. More recent prospective data on osteoporosis have shown prevalence rates between 21 and 25 % [10,18,28,29]. Loss of bone mineral density may occur even in early stages of the disease in connection with the inflammation process, independent of spine mobility and exercise [4,7,30].…”
Section: Spinal Remodeling In Asmentioning
confidence: 97%
“…Many studies have shown that OP is an important complication of AS that seriously affects the quality of life, even in young patients [3][4][5]32]. Various factors, such as [3,[7][8][9].…”
Section: Discussionmentioning
confidence: 98%
“…Men are more often affected than women, by a ratio of approximately 2-1 [1,2]. Osteoporosis (OP) is a wellknown feature of AS, even in the early, milder stages, and may cause spinal fractures and progressive spinal deformity [3][4][5]. The prevalence of OP in AS ranges from 18.7 to 62 % [6].…”
Section: Introductionmentioning
confidence: 98%
“…sacroiliac joints in AS or small joints of the hands in PsA. Common complications of AS are osteopenia, osteoporosis, and vertebral fractures, the latter often undiagnosed [5][6][7]. Low bone mineral density and osteoporosis can be detectable already within the first decade of the disease (in 51-54% and 13-16% of patients, respectively) [5].…”
Section: S U M M a R Ymentioning
confidence: 99%